VERTICAL INTEGRATION in AGRO-INDUSTRY: ECO-FRIENDLY GAMBIER PRODUCTS - Hamira, Hamira; Robiani, Bernadette; Mukhlis, Mukhlis (Journal of Economic Development, Environment and People, 2021)
Textile dyeing on fabrics and clothing causes environmental pollution and health problems. There is an innovation of natural coloring using gambier in the Gambo Muba fabric industry and the garment industry in Indonesia. Gambier farmers supply natural dye raw materials. Then through the supply chain of the Gambo Muba fabric industry and the garment industry, it causes vertical integration in the gambier agro-industry. This study uses primary data from 39 vertically integrated companies in the gambier agro-industry, including the gambier rubber industry, the Gambo Muba fabric industry, and the garment industry. The data was then analyzed using descriptive qualitative. This study analyzes the relationship between vertically integrated industries, including the transaction costs between them, their impact of vertical integration on added value, and their profitability. Vertically integrated industries have low transaction costs. The impact of vertical integration on the gambier agro-industry adds to the chain of economic activities that can increase added value and profits. The impact of vertical integration can reduce transaction costs, especially the supplier coordination cost component, distributor cost component, inter-company lobbying costs components. The benefits of vertical integration in the gambier agro-industry are increasing high added value, profit levels, decreasing environmental pollution, and agro-industry sustainability.